East Asian Integration Goods, Services and Investment - Ing, Lili Yan; Richardson, Martin; Urata, Shujiro (Routledge-ERIA Studies in Development Economics, 2019)
The growth of world trade has been stagnant in recent times; trade liberalisation now has been challenged. The recent rise of anti-globalisation calls for a better integration in East Asia. How should East Asia manage its openness? This book provides profound analyses on rules of origins, non-tariff measures, restrictiveness in services and investment. It gives insight into how East Asian countries should shape its trade, investment and industrial policies. This book helps to answer what kind of a better integration it should be, and how East Asia can realise it. "The Open Access version of this book, available at http://www.taylorfrancis.com/books/10.4324/9780429433603, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license."